Diversificação e bem-estar financeiro associados à qualidade de vida e saúde: um estudo com investidores brasileiros e regionais - Araújo, Flávia Barbosa de Brito (2021)
This study aims to investigate the relationship between the level of diversification and the quality of life and health, and to understand how financial well-being mediates this relationship. As a proxy for diversification, the sum of the types of assets in each investor's portfolio was adopted. The sociodemographic profile of the individuals in the sample was drawn, and the anxiety and depression scales from Beck's inventory (BAI and BDI) were used. Regarding the quality of life scale (QOL), the WHOQOL-100 was adopted. As an indicator of financial well-being (BEF) for the investor, the Credit Protection Service (SPC Brasil) measure was used, which follows the concept proposed by the Consumer Financial Protection Bureau (CFPB). The method of analysis involved structural equation modeling (SEM), estimated by Diagonal Weighted Least Squares (DWLS). This work was divided into two essays: (1) analysis of Brazilian investors; (2) analysis of regional investors subdivided into: 2.1. Minas Gerais, Goiás and Mato Grosso do Sul Group versus other states; and 2.2. Southeast Group versus other regions. For regional analysis, the structural model invariance test between groups was used. The chi-square differences were analyzed to measure the structural invariance and later for confirmation, the CFI variation was used, a metric considered more robust. For Essay 1 of this study, presented in Chapter 2 (Brazil level), the initial results for the SEM analysis showed a strong relationship of BEF mediation between the degree of diversification and the QLS, anxiety and depression scales. It is noteworthy that the BEF has a total mediation relationship between diversification and the other variables. In other words, the BEF contributes significantly and positively to diversification, on the other hand, it has a negative relationship with the anxiety and depression scales, and a positive relationship with the QOL. It can be said that the relationship between the diversification of assets in relation to the QLS scales, anxiety and depression, is indirect and is entirely mediated by the BEF. The results indicated age as a relevant variable, and confirmed the findings of the correlation between the age of the individuals in the sample and the classifications of depression, anxiety and QOL. It is concluded that the BEF totally mediates the other variables. A possible interpretation of the conclusion of the complete mediation between the BEF in relation to diversification, QOL, anxiety and depression, is that investors who have high levels of BEF, possibly do not depend on diversification to obtain quality of life, or even symptoms of anxiety. and depression. In relation to Trial 2 (Chapter 3 of this study), the results of the invariance test confirmed the invariance between the regions MG, GO and MS; Southeast and other regions. These results confirm that the scales employed in this research can be adopted to assess and compare BEF levels, quality of life and health, depression and anxiety, at the national and regional levels.